2013
DOI: 10.1186/1824-7288-39-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of allergic and respiratory symptoms in a regional cohort of extremely low birth weight children (<1000 g)

Abstract: BackgroundChildren who were <1000 g (ELBW extremely low birth weight) at birth more frequently present with wheezing which is the most common reason that pediatric consultation is sought. Therefore asthma is diagnosed very often. However is the asthma that is diagnosed in ELBW subjects atopic in origin, or is there a different etiology?AimTo determine if ELBW infants are at higher risk for the development of allergic and respiratory symptoms and to establish if there were any specific risk factors for these sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Many of them try to answer the question of whether the BPD and/or preterm birth are risk factors for asthma 411 , 21 , 26 As found in the present study, other authors have observed a higher prevalence of asthma in VLBW infants when compared with the prevalence of asthma in the world population,7 , 11 , 19 , 22 , 27 with values for extremely premature infants ranging between 26%5 , 19 , 27 and 40% 22…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Many of them try to answer the question of whether the BPD and/or preterm birth are risk factors for asthma 411 , 21 , 26 As found in the present study, other authors have observed a higher prevalence of asthma in VLBW infants when compared with the prevalence of asthma in the world population,7 , 11 , 19 , 22 , 27 with values for extremely premature infants ranging between 26%5 , 19 , 27 and 40% 22…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, the effects of BPD in the onset of atopy, asthma, and/or recurrent wheezing at older ages is controversial 34 , 9 , 13 , 15 , 16 The effect of BPD in lung function in the long term has been evaluated in numerous age groups, including newborns,17 infants,18 preschoolers,19 schoolchildren,7 - 11 adolescents,12 - 14 and adults 2022 Studies have shown reduced lung volumes in different age groups, but with low association to clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…They comprised 6 birth cohorts [17][18][19][20][21][22] and 19 population-based longitudinal studies. [12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Tables 1 and 2 give an overview of the included studies. The reasons for rejecting the remaining 30 papers [9,10, are summarised in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were included in our review .Three of the five risk factor combinations investigated showed a significant association with subsequent low lung function. [18,29,30,37] The longest duration of follow-up in those studies was 12 years. A 21 year follow-up study of babies born extremely prematurely has reported that any differences in lung function compared with termborn controls during childhood disappears in adult life.…”
Section: Page 13 Of 24mentioning
confidence: 99%
“…Thus, different pathophysiological mechanisms, other than allergic sensitization, are proposed to underlie the increased risk of asthma and wheezing disorders following preterm birth. This hypothesis has been supported by studies describing the lack of association between allergic sensitization, viral infection and the risk of asthma and diminished lung function later in life among preterm-born children [116118]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 85%